Efficacy of Plyometric Exercises Versus Wii Training on Upper Extremity Function in Children with Unilateral Cerebral Palsy: A Comparative Study - Saad-Eldien, Sara S; El-Shamy, Shamekh Mohamed; Sayed, Asmaa O; Ibrahim, Ahmed Abdelmoniem; Abd-Elmonem, Amira M; Abd El-Nabie, Walaa A; Abd-Elwahab, Heba H; Hassan, Faten Mohamed; Abd-Elfattah, Hanaa Mohsen (NeuroRehabilitation (Reading, Mass.), 2025)
ObjectivesTo compare between the effects of plyometric exercises versus Wii on upper extremity functions in children with unilateral cerebral palsy (UCP).MethodForty-two children with UCP, ranging in age from 8 to 12 years were allocated to receive plyometric exercises (PLYO -group) or Wii training (Wii-group) for 45 min. both groups received selected occupational therapy programs for 30 min twice a week over 3-month. The intervention was delivered on non-consecutive days. The quality of upper extremity skills test (QUEST), Test of arm selective control (TASC) and pneumatic squeeze bulb dynamometer were used to assess upper extremity function, SMC and HGS, respectively.ResultsOverall, 42 children (21 in the PLYO-group, 21 in the Wii-group) completed data collection and treatment. With-in group comparison showed significant improvement in both groups while post-treatment comparisons revealed a significant difference from mean difference in upper extremity function is 9.55 (8.71:10.39), SMC is 2.05 (1.47: 2.63) and HGS is 2.86 (2.20: 3.53) ( < 0.05; 95% Confidence interval) in favor of the PLYO-group.ConclusionsPlyometric exercises are significantly more effective than Wii training in improving upper extremity function and strength in children with UCP.